Investigation on bending strength and stiffness of sugar palm fibre from different parts reinforced unsaturated polyester composites. - Salit, Mohd Sapuan; Ab. Rahman, Mohamad Zaki; Zahari, Nur Ismarrubie; Japar, Sahari (Trans Tech Publications, 2011)
This investigation is done to select the best composite on bending strength and stiffness derived from different parts of sugar palm fibre reinforced unsaturated polyester composites. Sugar palm tree is one of the most popular natural fibres. The fibre was obtained from the sugar palm tree and mixed with unsaturated polyester (PE). All of the composites are labelled as SPF/PE for sugar palm frond composite, SPB/PE for sugar palm bunch composite, SPT/PE for sugar palm trunk composite and ijuk/PE for black sugar palm fibre composite. The bending strength and stiffness tests were done according to ASTM D 790-(2000). The higher value of bending strength and stiffness obtained by SPT/PE which is 41.906 MPa and 3.363 GPa respectively followed by SPF/PE (38.906 MPa and 3.001 GPa), SPB/PE (35.168 MPa and 2.749) and ijuk/PE (33.742 MPa and 2.424 GPa)